Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.